Elucidating the role of the heterojunction interface in the exciton harvest and charge collection of organic solar cells through a planar heterojunction structure. Issue 2 (13th December 2021) - Liang, Quanbin; Xie, Yuan; Wu, Hongbin
Abstract : The exciton harvest and charge collection of non-fullerene organic solar cells were investigated in a contact-film-transfer fabricated planar structure, which was proven to be an excellent platform for comprehensive studies of the interface. Abstract : The rapid progress in the development of non-fullerene electron acceptors has led to key breakthroughs in the power conversion efficiency of organic solar cells (OSCs). Nevertheless, the development of non-fullerene OSCs is still hindered by a lack of deep understanding of the heterojunction interface, where charge generation and recombination occur. Here, we use a solution-based contact film transfer method to fabricate a planar heterojunction (PHJ) device, which serves as an excellent platform to investigate exciton harvest and charge collection owing to the clearly defined interface. By reconstructing the external quantum efficiency spectra and device modeling in PHJ cells based on a large bandgap polymer J52 and a low bandgap small molecule IEICO-4F, exciton diffusion lengths of 9.2 nm and 7.5 nm are extracted for J52 and IEICO-4F, respectively. The experimentally obtained values for the exciton diffusion length confirm that the BHJ structure is an important prerequisite for efficient organic solar cells. Nevertheless, as revealed by the carrier dynamic studies, BHJ devices could suffer from severe recombination losses as a result of energetic disorder and traps. By considering the recombination of free and trapped carriers and intermediates in the photocurrent generation processes, we show that the stronger recombination of the BHJ compared to the PHJ is also related to its shorter CT state lifetime and lower CT state density based on the reduced Langevin recombination analysis. The inherent limitation in BHJ devices is thus a major disadvantage that needs to be overcome for further improvement. Therefore, fine tuning of the D/A interface in non-fullerene OSCs plays a crucial role in controlling the device performance. Our work also demonstrated that the contact film transfer method holds great potential for detailed studies of the heterojunction interface in the future.